2004
DOI: 10.1177/000992280404300811
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Breast-feeding and Parental Intelligence on Cognitive Development in the 24-Month-Old Child

Abstract: This study was designed to analyze the relationship between breast-feeding and mental development at 24 months of age, independently of the influence of other factors. A total of 238 babies born between October 1995 and February 1998 were enrolled in an observational prospective cohort study. Cognitive development was assessed using the Bayley Infant Development Scale. The results of multiple linear regression analysis showed that infants breast-fed for longer than 4 months scored 4.3 points higher on the ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 30 publications
(30 reference statements)
0
28
1
Order By: Relevance
“…Most of these studies find (short-run) positive effects of longer breast-feeding (Kramer et al, 2008;Gómez-Sanchiz et al, 2004;Elwood et al, 2005;Richards et al, 2002) whereas other studies find no effect when controlling for family background information (Silva et al, 2006;Zhou et al, 2007). 4 The results in these studies cannot always be generalized, though.…”
Section: Previous Evidence On Child Outcomes and Parental Leavesmentioning
confidence: 97%
“…Most of these studies find (short-run) positive effects of longer breast-feeding (Kramer et al, 2008;Gómez-Sanchiz et al, 2004;Elwood et al, 2005;Richards et al, 2002) whereas other studies find no effect when controlling for family background information (Silva et al, 2006;Zhou et al, 2007). 4 The results in these studies cannot always be generalized, though.…”
Section: Previous Evidence On Child Outcomes and Parental Leavesmentioning
confidence: 97%
“…The maternal nutrition is very important during lactation, and it is at the forefront of priorities in health programs [3]. The components of the breast milk promote infants' protection against infectious diseases, increasing the intelligence quotient (IQ) as well as the emotional and psychological development of the infants [4]. Lack of exclusive breastfeeding, mostly during the first 6 months, leads to more than one million preventable deaths annually [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal smoking during pregnancy has been related to impaired cognitive development [21]. In a study on 2-year-old children, Gómez-Sanchiz et al reported that the parents' educational background and family's social class were related to the child's mental development [22]. Developmental delays in 1-year-old children (12-18 months) have been reported to be correlated with maternal depression during pregnancy [23].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that long-chain polyunsaturated fatty acids, docosahexaenoic acid, and arachidonic acid, all found in breast milk, support neuron development [40]. Moreover, increased maternal responsiveness promoted by the infant's suckling [41] also has a favorable effect on infant development, and mothers who engage in breast-feeding are generally more educated than formula-feeding mothers [22]. This also may have a favorable effect on infant development.…”
Section: Type Of Deliverymentioning
confidence: 99%